2013
DOI: 10.1016/j.molcel.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

An MRAS, SHOC2, and SCRIB Complex Coordinates ERK Pathway Activation with Polarity and Tumorigenic Growth

Abstract: SHOC2 is mutated in Noonan syndrome and plays a key role in the activation of the ERK-MAPK pathway, which is upregulated in the majority of human cancers. SHOC2 functions as a PP1-regulatory protein and as an effector of MRAS. Here we show that SHOC2 and MRAS form a complex with SCRIB, a polarity protein with tumor suppressor properties. SCRIB functions as a PP1-regulatory protein and antagonizes SHOC2-mediated RAF dephosphorylation through a mechanism involving competition for PP1 molecules within the same ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 43 publications
7
137
0
1
Order By: Relevance
“…Additionally, gain-of-function RAF1 mutations cause NS. In fact, these mutations seem to cluster around the S259 phosphorylation site, emphasizing the importance of MRAS/SHOC2/PP1C-mediated dephosphorylation of RAF1's serine residue at amino acid 259 in RAF/ERK/MAPK pathway activation and associated disease pathogenesis (9,30,31). Our data suggest that activating mutations in MRAS similarly lead to enhanced Ras/MAPK pathway signaling, likely through the activity of this MRAS/SHOC2/PP1C complex.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Additionally, gain-of-function RAF1 mutations cause NS. In fact, these mutations seem to cluster around the S259 phosphorylation site, emphasizing the importance of MRAS/SHOC2/PP1C-mediated dephosphorylation of RAF1's serine residue at amino acid 259 in RAF/ERK/MAPK pathway activation and associated disease pathogenesis (9,30,31). Our data suggest that activating mutations in MRAS similarly lead to enhanced Ras/MAPK pathway signaling, likely through the activity of this MRAS/SHOC2/PP1C complex.…”
Section: Discussionmentioning
confidence: 70%
“…The removal of this inhibitory phosphate stimulates Raf1 activity and, thereby, activity of downstream MAPK pathway signaling (29). MRAS, therefore, makes a critical contribution to ERK activation by receptor tyrosine kinases and downstream MAPK signaling (30). Mutations in the other components of this ternary complex, SHOC2 and PP1, have been implicated previously in the pathogenesis of RASopathies.…”
Section: Discussionmentioning
confidence: 99%
“…The scaffold protein Shoc2 was shown to accelerate ERK1/2 activity by bringing several signaling proteins in close proximity: H-, N-, K-and M-Ras, RAF-1, PP1c, and the recently identified member of the LAP protein family SCRIB (8,12,42,61). We previously showed that, in addition to its function as an ERK1/2 pathway signaling accelerator, Shoc2 integrates a negative ERK1/2 feedback loop that inhibits ERK1/2 signals.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Scribble with PP1γ is required for Scribble's ability to downregulate ERK phosphorylation and for Scribble to prevent oncogenic transformation of primary rodent cells. Scribble has also been shown to form a complex with SHOC2/SUR-8 (PP1 phosphatase regulator) and MRAS (RRas subgroup of Ras proteins), and Scribble blocks SHOC2-mediated dephosphorylation of RAF (a protein kinase downstream of Ras) at the conserved inhibitory site (S259), thereby inhibiting RAF activation (Young et al 2013). This mechanism appears to be conserved in Drosophila, where the deregulation of PP1 activity contributes to the scrib mutant phenotype, but in this case it appears to function via regulation of the JNK stress response signaling (Jiang et al 2011).…”
Section: Rtk-ras-mapk/jnk/p38mentioning
confidence: 99%